Responsabilidade tributária : o terceiro como sujeito passivo da obrigação - Gomes Neto, Alfredo (2010)
With this work it will be looked to study the beginning tax liability, as it imposes the Internal revenue code - Law 5,172, of 25 of October of 1966 -, more, especially interpolated proposition III of article 135 of this statute and its influence before interpolated proposition V of the article 4º of the Law of Tax foreclosure - Law 6,830, of 22 of September of 1980 - that, of generalized form, does not specify and nor individualiza the situations where each passive citizen is seen as responsible by the tax debit. The starting point of all the work is the deepening of the study of the substance responsibility , with a proposal of new vision and proposal of its study before the right and, thus, it becomes necessary to study the tribute as legal form of obligation imposition and as, the formation of the credit tributary and its quarrel inside of the administrative proceeding tributary, to arrive the formation of the extrajudicial heading, with the responsibility staff of the partner, administrator or controlling for practical of action or the contrary omission the law, statute or with power excess that it has been the cause of lacks of obligation fulfilment tax, fully determined - registration in the active debt of the Tributante Being -, and, thus, to make the execution of the debit in accordance with the Law of Tax foreclosure . Finally, the conclusion of that: The responsibility staff of the agent chief executives, chairmen and used by the corresponding credits the obligations taxes, resultants of acts practised with excess of being able or infraction of law, social contract or subjective statutes must be refined of form, through the fiscal administrative proceeding, respecting the constitucional law of due process of law, either judicial or administrative, of legal defense and the contradictory